Chemical composition and in vitro ruminal fermentation of common tree forages in the semi-arid range lands of India - SANTRA, A; KARIM, S A (The Indian Journal of Animal Sciences, 2019)
The objective of study was to look for the promising tree leaves for feeding livestock particularly the small ruminants. Ten tree leaves were collected from semiarid region of Rajasthan and evaluated for their nutritional quality in terms of chemical composition as well as in vitro dry matter and organic matter digestibility (IVDMD and IVOMD). Most of the tree leaves were rich in CP content. OM, CP and ADF content of these collected tree leaves varied from 87.1 to 92.5%, 9.4 to 19.8% and 22.7 to 47.9% on DM basis, respectively. Rumen protozoal number decreased due to inclusion of Sapindus mukorossi, Azadirachta indica and Prosopis cineraria tree leaves in the incubation media. IVDMD, IVOMD, TVFA and propionate production significantly higher for Ailanthus excelsa tree leaves followed by Acacia arabica and Acacia senegal tree leaves. All the tested tree leaves had no effect on Î²-glucosidase and amylase enzyme activity. However, specific activity of carboxymethyl cellulase and xylanase reduced significantly due to addition of Sapindus mukorossi, Azadirachta indica and Prosopis cineraria tree leaves in the incubation medium. The results indicated that among the tree leaves tested in the present study Ailanthus excelsa, Acacia arabica and Acacia senegal are good tree fodder for feeding to the ruminants.